Multi-criteria assessment model to identify suitable areas for treated wastewater reuse in agriculture - Gatto D'andrea, María Laura (2021)
A model of land suitability analysis for irrigation with treated domestic wastewater is presented. The model integrates tools of Multi-Criteria Evaluation with Geographical Information Systems. Several criteria were selected to adapt the model to the condi-tions and characteristics of the case study. The adaptation process included field visits, a bibliographical review, and personal interviews with local actors and experts. Six constraints and 10 factors were selected and 3158 hectares suitable for the activity were identified. The areas were classified into three categories of aptitude, representing high fitness sites close to the current wastewater treatment plant. The developed tool allowed us to integrate different criteria to assess site suitability for wastewater reuse, with the advantage that the tool can be adapted to other regions and/or objectives.